Development of a maximum power point tracking system for solar lighting applications - Peiris, T. C.; Sonnadara, D.U.J.; Ariyaratne, T.R. (University of Colombo, 2010)
In the power sector of Sri Lanka, 65% of the required energy is generated by using Fuel sources. Since all necessary fuel to generate electricity is imported from other countries, the unit cost of generating electricity is very high. Renewable sources such as solar power and small scale hydro power have emerged as an economical and sustainable alternative source to promote medium term electricity generation especially to rural communities. Since Sri Lanka is situated close to the Equator, solar radiation over the island does not show high seasonal variability. The average solar radiation remains at 5.0 kilo Watthour/square meter/day, and thus, substantial potential exists for harvesting renewable solar energy. In this work, a smart charge controller was developed and tested for Solar lighting applications. The smart charge controller is mainly designed for a battery charging application which is controlled through a low cost, low power consumption PIC16F877A microcontroller. The charging current is used to change the duty cycle of the dc/dc converter control signal. The smart charge controller uses the Maximum Power Point Tracking (MPPT) technique to obtain the optimum results. The results show that the MPPT process increases the charging current. The measurements show that percentage increase in charging current compared to the 12.5 V regulations is above 100% even under cloudy conditions.